Menopause and work: an electronic survey of employees’ attitudes in the UK - Griffiths, Amanda; MacLennen, Sara Jane; Hassard, Juliet (Elsevier, 2013)
Objectives: This study explored women's experiences of working through menopausal transition in the UK. It aimed to identify the perceived effects of menopausal symptoms on working life, to outline the perceived effects of work on menopausal symptoms, and to provide recommendations for women, healthcare practitioners and employers.